Case Report: Transoral Endoscopic Thyroidectomy via Vestibular Approach in Pediatric Thyroid Cancer - Ngo, Duy Q.; Le, Duong T.; Hoang, Giap N.; Ngo, Quy X.; Le, Quang V. (Frontiers in Pediatrics, 2021)
Background: Transoral endoscopic thyroidectomy via vestibular approach (TOETVA) is a new technique that has become more popular worldwide because of its many advantages. However, this novel approach for thyroid cancer treatment in children is highly challenging, even for high-volume surgeons. In our study, we report our experiences with TOETVA for pediatric patients with thyroid cancer. Patients and Methods: This study included four pediatric patients who underwent TOETVA performed by a single surgeon between June and December 2020. Patient demographics and surgical outcomes including operative time, incidence of complications, and length of hospital stay were evaluated. Results: Four patients successfully underwent TOETVA with no complications. All patients were girls, aged from 13 to 18. Three patients underwent lobectomy and isthmusectomy, plus prophylactic unilateral central neck dissection. One patient had a total thyroidectomy, plus prophylactic bilateral central neck dissection. The mean operative time was 85 mins for the lobectomy and 120 mins for total thyroidectomy plus central neck dissection. The median hospital stay was 4.1 days. No drains were used. The histological examination showed four cases of malignant disease (papillary thyroid carcinoma). The mean number of harvested lymph nodes was 4.2 (ranged 3 to 8). Conclusion: In the hands of a high-volume surgeon, TOETVA is a novel, feasible and safe approach for treating selected pediatric patients with thyroid cancer.